Requirement Analysis and Problem Finding Using Design Thinking Concepts in Students’ Information System Projects - Nurul Zawiyah, Mohamad; Missie, Chundau; Francis Zhi Yang, Yii (IEEE, 2022)
Developing an information system from scratch involves finding the true problem of users and doing proper analysis of their requirements. However, it is very common for users not receiving an information system or management system that fully solves all their problems. We believe the requirement analysis stage is crucial and traditional system development lifecycles are not involving the users enough throughout the lifecycle, hence causing a subpar outcome especially in student’s final year project. In this paper, we present a way to do requirement analysis and problem finding by using design thinking concepts and apply it to students’ first phase of final year project. Two case studies of current students are presented in this paper and their deliverables of strategies used respective stages are shown. According to these students, by applying design thinking in their requirement analysis stage and involving their users in the loop, they have a better understanding on the foundation of their users’ problems and can come up with a proper proposed solution.